Durability characteristics and quantification of ultra-high strength alkali-activated concrete. (November 2022) - Cai, Rongjin; Tian, Zushi; Ye, Hailong
Abstract: Clinkerless ultra-high strength concrete formulated using alkali-activated binders (AAB-UHSC) emerges as a green high-performance construction material, but its durability characteristics have not been systematically investigated yet. In this work, the resistances of AAB-UHSC against water absorption, carbonation, chloride diffusion, and chloride-induced electrochemical corrosion of steel, are quantitatively evaluated and compared with those of ordinary Portland cement (OPC)-based UHSC and normal-strength AAB (AAB-NSC) counterparts. The results show that in comparison with OPC-UHSC of similar strength of ∼150 MPa, AAB-UHSC has lower water-permeable porosity and demonstrates superior performance against water absorption and chloride ingress, but a weaker carbonation resistance. However, despite lower CO2 uptake capacity, the carbonation resistance of AAB-UHSC is about six times stronger than that of AAB-NSC, owing to its highly densified microstructure. Under the same chloride level and relative humidity conditions, the corrosion rate of steel embedded in AAB-UHSC is higher than that in OPC-UHSC, likely due to its higher moisture content and [Cl − ]/[OH − ] ratio that expedite steel dissolution. Moreover, the incorporation of steel fibers has limited influence on the transport-related durability performance of AAB-UHSC, implying a densified interfacial zone between steel fibers and AAB-UHSC matrices.